The Effect of Exclusive Breastfeeding on Wasting in Children Under Five: A Meta-Analysis Study - Wijiwinarsih, Amallia; Susilawati, Tri Nugraha; Murti, Bhisma (Journal of Maternal and Child Health, 2019)
Background: Wasting is a form of malnutrition that has become a serious global health problem for the past few decades. Global prevalence of wasting is reported to reach 52 million or 7.7% of the under-fives. Global coverage of exclusive breastfeeding was still as low as 40%. The purpose of this study was to due a meta-analysis on the effect of exclusive breastfeeding on wasting in children under five. Subjects and Method: This was a meta-analysis study conducted from PubMed, SCOPUS, DOAJ, BASE, EBSCO, Emerald, ProQuest, ScienceDirect, ResearchGate, and Google Scholar databases. This study sought a systematic review with observational study design and multivariate-adjusted odds ratio (AOR) analysis. Wasting was defined as weight for height (WHZ) Z score <-2. The data were analyzed by RevMan 5 meta-analysis program with a fixed effect and random effect analysis model. Results: There were 13 articles included in this study. Based on 3 study design, exclusive breastfeeding could prevent the risk of wasting in children under five with each meta-analysis result from a cross-sectional study 0.42 times (OR = 0.42; 95% CI = 0.28 to 0.62; p <0.001), case-control studies 0.38 times (OR = 0.38; 95% CI = 0.27 to 0.54; p <0.001), and cohort studies 0.75 times (OR = 0.75; 95% CI = 0.55 to 1.04; p = 0.08). There was no publication bias in the results of the cross-sectional and case-control study meta-analysis, but there was in the results of the meta-analysis of the cohort study. Conclusion: Exclusive breastfeeding can prevent wasting in children under five. Keywords: exclusive breastfeeding, wasting, observational study Correspondence: